Integrating RNA-seq and scRNA-seq to explore the mechanism of macrophage ferroptosis associated with COPD - Fan, Pengbei; Zhang, Yige; Ding, Shenao; Du, Zhixin; Zhou, Chunyu; Du, Xiaodan (Frontiers in Pharmacology, 2023)
Aims: Our study focused on whether macrophages ferroptosis is associated with the pathogenesis of chronic obstructive pulmonary disease (COPD) or not. Main methods: We first identified macrophage module genes by weighted gene co-expression network analysis (WGCNA) in RNA sequencing (RNA-seq) date from COPD, and then identified macrophage marker genes by comprehensive analysis of single-cell RNA sequencing (scRNA-seq) data from COPD macrophages. There were 126 macrophage marker genes identified, and functional enrichment analyses indicated that ferroptosis pathway genes were significantly enriched. Secondly, we identified eight macrophage ferroptosis related genes and based on these eight genes, we performed co-expression analysis and drug prediction. Thirdly, two biomarkers (SOCS1 and HSPB1) were screened by the least absolute shrinkage and selection operator (LASSO), random forest (RF), and support vector machine-recursive feature elimination (SVM-RFE) and established an artificial neural network (ANN) for diagnosis. Subsequently, the biomarkers were validated in the dataset and validation set. These two biomarkers were then subjected to single gene-gene set enrichment analysis (GSEA) and gene set variation analysis (GSVA) analysis, and the ceRNA network was constructed. Finally, we carried out molecular validation with COPD models in vitro for cell counting kit-8 (CCK8) experiments, Western Blot and quantitative real-time PCR (qRT-PCR) analysis and transmission electron microscopy (TEM). Key findings: This study revealed the vital role of macrophage ferroptosis in COPD, and novel biomarkers (SOCS1 and HSPB1) may be involved in the pathogenesis of COPD by regulating macrophage ferroptosis. Significance: Taken together, our results suggest that targeting SOCS1 and HSPB1 could treat COPD by inhibiting macrophage ferroptosis.